Can real-time polymerase chain reaction allow a faster recovery of hospital activity in cases of an incidental discovery of carbapenemase-producing Enterobacteriaceae and vancomycin-resistant Enterococci carriers?. Issue 2 (October 2019) - Saliba, R.; Neulier, C.; Seytre, D.; Fiacre, A.; Faibis, F.; Leduc, P.; Amara, M.; Jauréguy, F.; Carbonnelle, E.; Zahar, J.-R.; Marty, L.
Summary: Background: Detection of faecal carriers of carbapenemase-producing Enterobacteriaceae (CPE) and vancomycin-resistant Enterococci (VRE) has become a routine medical practice in many countries. In an outbreak setting, several public health organizations recommend three-weekly rectal screenings to rule-out acquisition in contact patients. This strategy, associated with bed closures and reduction of medical activity for a relatively long time, seems costly. Aim: The objective of this study was to test the positive and negative predictive values of reverse transcription polymerase chain reaction (RT-PCR; GeneXpert®) carried-out at Day 0, compared with conventional three-weekly culture-based rectal screenings, in identifying, among contact patients, those who acquired CPE/VRE. Methods: A multicentre retrospective study was conducted from January2015 to October2018. All contact patients (CPs) were included identified from index patients (IPs) colonized or infected with CPE/VRE, incidentally discovered. Each CP was investigated at Day 0 by PCR (GeneXpert®), and by the recommended three-weekly screenings. Findings: Twenty-two IPs and 159 CPs were included. An average of 0.77 secondary cases per patient was noted, with a mean duration of contact of 10 days (range 1–64). Among the 159 CPs, 16 (10%) had a CPE/VRE-positive culture during the monitoring period. Rectal screenings were positive at Day 0 (10 patients), Day 7 (two patients), Day 14 (four patients). Thirteen of 16 patients with positive culture had a positive PCR at Day 0. Overall, a concordance of 97.5% (155/159) was observed between the three-weekly screenings and Day 0 PCR results. When performed on CPs at Day 0 of the identification of an IP, PCR (GeneXpert®) allowed the reduction in turnaround time by five to 27 days, compared to three-weekly screenings. Positive predictive value and negative predictive value were 100% and 98%, respectively. Conclusions: The use of RT-PCR (GeneXpert®) can avoid the three-weekly rectal samplings needed to rule-out acquisition of CPE/VRE.